2007
DOI: 10.1099/ijs.0.64755-0
|View full text |Cite
|
Sign up to set email alerts
|

Coraliomargarita akajimensis gen. nov., sp. nov., a novel member of the phylum ‘Verrucomicrobia’ isolated from seawater in Japan

Abstract: Coraliomargarita akajimensis gen. nov., sp. nov., a novel member of the phylum 'Verrucomicrobia' isolated from seawater in Japan An obligately aerobic, Gram-negative, non-spore-forming, non-motile, spherical bacterium, designated strain 04OKA010-24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 21 publications
1
56
1
Order By: Relevance
“…The data from this study suggest that the different bacterial morphotypes are different taxa occupying separate tubules. Bacterial morphology by itself is not a reliable taxonomic identifier; however, studies of the marine verrucomicrobium Coraliomargarita akajimensis revealed a morphology similar to the LCB morphotype observed in this study (52). The two epithelial morphologies of the ANG tubules are very distinct from one another, suggesting that each tubule fosters a unique microenvironment optimized to contain a specific bacterial taxon or that specific bacteria influence development of different epithelia.…”
Section: Discussionmentioning
confidence: 41%
“…The data from this study suggest that the different bacterial morphotypes are different taxa occupying separate tubules. Bacterial morphology by itself is not a reliable taxonomic identifier; however, studies of the marine verrucomicrobium Coraliomargarita akajimensis revealed a morphology similar to the LCB morphotype observed in this study (52). The two epithelial morphologies of the ANG tubules are very distinct from one another, suggesting that each tubule fosters a unique microenvironment optimized to contain a specific bacterial taxon or that specific bacteria influence development of different epithelia.…”
Section: Discussionmentioning
confidence: 41%
“…There are nine validly named species within the class Opitutae (subdivision 4) (6,7,56,(58)(59)(60). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Strain 04OKA010-24 T (DSM 45221 = JCM 23193 = KCTC 12865) is the type strain of the species Coraliomargarita akajimensis and was first described in 2007 by Yoon et al [1]. Strain 04OKA010-24 T was isolated from seawater surrounding the hard coral Galaxea fascicularis L., collected at Majanohama, Akajima, Okinawa, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the genus Coraliomargarita [1] the genera Cerasicoccus [10], Pelagicoccus [11], Puniceicoccus [9] belong into the family Puniceicoccaceae . Here we present a summary classification and a set of features for C. akajimensis 04OKA010-24 T , together with the description of the complete genomic sequencing and annotation.…”
Section: Introductionmentioning
confidence: 99%